Feminisme dalam Cerpen Musim Dingin yang Kejam Karya Ade Mulyono - Santoso, Akhmad Aji; Pratama, Wildhan (Bastrando: Jurnal Bahasa dan Sastra Indonesia, 2024)
This research aims to describe forms of injustice, gender, violence, marginalization of women and issues of feminism found in short stories Musim Dingin yang Kejam Ade Mulyono. This research uses a descriptive method where the author first reads the contents of the short story before analyzing it, then analyzes the issue of feminism in the short story. Based on the results of the analysis, this short story shows that feminism is deeply embedded in society and the cruelty of society's view of women. Gender differences have always been a stronghold of separation that tends to restrain a woman's freedom of activity and expression. This research is clear evidence of how different people's perspectives are gender. Differences in gender is the cause of inequality and violence, especially against women. The existing culture, traditions and habits that place women in a position below men are defined as feminism.